2017
DOI: 10.1891/1945-8959.16.3.241
|View full text |Cite
|
Sign up to set email alerts
|

The Testing Effect and Its Relation to Working Memory Capacity and Personality Characteristics

Abstract: Retrieval practice is known to lead to better retention of a to-be-learned material than restudy (i.e., the testing effect). However, few studies have investigated retrieval practice in relation to working memory capacity (WMC) and personality characteristics such as grittiness (Grit) and need for cognition (NFC). In two experiments, we examined retrieval practice and restudy of Swahili–Swedish word pairs in relation to individual differences in Grit and NFC. In Experiment 1, using a between-subjects design, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(64 citation statements)
references
References 50 publications
5
56
3
Order By: Relevance
“…In the present study, we found several single features that significantly predicted verbal WM performance. One of those features was multiple-choice quizzes, indicating that individuals with higher quiz accuracies performed better in the Digit span (Wiklund-Hörnqvist et al, 2014;Bertilsson et al, 2017). Reflecting this finding to the multicomponent model of WM (Baddeley and Hitch, 1974), one could speculate whether this association mirrors differences in how effectively the subvocal rehearsal and the phonological loop is utilized, both when reading the to-be-learned materials, as well as when performing the WM task.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the present study, we found several single features that significantly predicted verbal WM performance. One of those features was multiple-choice quizzes, indicating that individuals with higher quiz accuracies performed better in the Digit span (Wiklund-Hörnqvist et al, 2014;Bertilsson et al, 2017). Reflecting this finding to the multicomponent model of WM (Baddeley and Hitch, 1974), one could speculate whether this association mirrors differences in how effectively the subvocal rehearsal and the phonological loop is utilized, both when reading the to-be-learned materials, as well as when performing the WM task.…”
Section: Discussionmentioning
confidence: 89%
“…It has, for instance, been shown that low WM individuals have poorer performances in school subjects such as arithmetics (Gathercole and Pickering, 2001;Swanson and Beebe-Frankenberger, 2004;Raghubar et al, 2010), and reading comprehension (Daneman and Carpenter, 1980;Turner and Engle, 1989). It has also been found that those with poorer WM performance tend to perform worse in quiz tasks assessed immediately following the learning phase (Wiklund-Hörnqvist et al, 2014;Agarwal et al, 2017;Bertilsson et al, 2017), including poorer performances in final course exams (Turner and Engle, 1989;Aronen et al, 2005;Cowan et al, 2005). As for the more specific differences in learning activities, WM has shown to predict how frequently the learner goes back and repeat earlier learned materials such that those with poorer WM tend to go back and read earlier material more frequently as compared to those with better WM performance (Rosen and Engle, 1997;Kemper et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research on skill acquisition and performance has increased the amount of interest in the combination of cognitive measures and measures of personality [ 27 ]. Several different perspectives apply to the understanding of personality ; thus, there are many definitions and theories encompassing personality, including cognitive, humanistic and sociocultural ones [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…WMC is an interesting individual-differences variable in cognitive psychology because it accounts for a substantial portion of variance in a person's general fluid intelligence and executive function (see Conway, Kane, & Engle, 2003;Foster et al, 2015;McCabe, Roediger, McDaniel, Balota, & Hambrick, 2010). The majority of these studies found no (direct) relationship between WMC and the backward testing effect effect (Agarwal, Finley, Rose, & Roediger, 2017;Aslan & Bäuml, 2011) or test-potentiated learning (Bertilsson, Wiklund-Hörnqvist, Stenlund, & Jonsson, 2017;Brewer & Unsworth, 2012;Minear, Coane, Boland, Cooney, & Albat, 2018;Tsu & Pu, 2012;Wiklund-Hörnqvist, Jonsson, & Nyberg, 2014; but see Agarwal et al, 2017). Notably, the study by Tse and Pu (2012) showed that a significant proportion of variance in test-potentiated learning could be predicted by an interaction between participants' WMC and test anxiety scores.…”
Section: Introductionmentioning
confidence: 99%